Tramas e urdiduras : o protagonismo como exercício na atividade de professores de educação física - Almeida, Ueberson Ribeiro (2014)
The work is an intervention research with main purpose to analyze how Teachers carry out the protagonist exercise in practice. It is mainly based on the conceptual contribution of Yves Schwartz ergological perspective to perform the analysis of the school daily life activity. The study was held at a Municipal Elementary School located in the district of Serra/ES with the participation of two Physical Education female Teachers and a male one. The methodological strategies used were constituted of the activity follow up developed by the Teachers in the classes, of the PE permanent formation course promoted by the Municipal Education Secretariat, participation in the school everyday life through body practice workshops. The production techniques and data records were composed by a field diary, pictures, audio recorded talks, interviews, a questionnaire and documents elaborated by the school, such as the Pedagogical Political Project. The data confrontation carried out with the Teachers in the conversations, produced important displacement in the analyzes and called authors and concepts that were not expected in the debate on the protagonist exercise. Data production created a change in the Teachers practice and put in question the management ways and the work organization in the Education Network of Serra, causing transformations in the permanent formation models of the PE Teachers in the district. The protagonist exercises undertaken in the Teachers’ practice put competences in circulation and made visible the plot and warp effects that crossed and compose the PE Teachers practice in the school daily life.